La creatividad y el arte en niños y niñas de tres, cuatro y cinco años de la institución educativa inicial N°602, San Juan Bautista 2022 - Armas Rioja, Sandra Paola (2024)
The objective of this research is to explore the connection between creativity and art in three, four and five-year-old children of the Institución Educativa Inicial N°602 San Juan Bautista during the year 2022. This study adopted a quantitative approach and was framed in relational research with a non-experimental design. The population was made up of a total of 95 children of the aforementioned ages. For data collection, the observation technique was used and an observation guide was used, which was validated by three experts in the field. The results obtained through Spearman's evaluation showed a coefficient of 0.722 and a bilateral significance of 0.05, confirming a positive and significant activation between creativity and art. This validates the hypothesis that there is a relationship between creativity and art in three, four and five year old children from the Initial Educational Institution No. 602.